3.9k views
3 votes
Which best proves why the expressions 4 (x + 3) + 2 x and 6 (x + 2) must be equivalent expressions?

When x = 3, both expressions have a value of 30.
When x = 5, both expressions have a value of 42.
When x = 1, both expressions have a value of 18, and when x = 8, both expressions have a value of 60.
When x = 2, both expressions have a value of 15, and when x = 6, both expressions have a value of 39.

User NightRa
by
5.5k points

1 Answer

2 votes

Answer:

When x=1

Explanation:

Solving for both equations by putting them both equal to each other.

User Matoeil
by
5.9k points